Effect of Different Catalyst Deposition Technique on Aligned Multiwalled Carbon Nanotubes Grown by Thermal Chemical Vapor Deposition. (9th April 2014) - Mohamed Saheed, Mohamed Shuaib; Mohamed, Norani Muti; Burhanudin, Zainal Arif
Abstract : The paper reported the investigation of the substrate preparation technique involving deposition of iron catalyst by electron beam evaporation and ferrocene vaporization in order to produce vertically aligned multiwalled carbon nanotubes array needed for fabrication of tailored devices. Prior to the growth at 700°C in ethylene, silicon dioxide coated silicon substrate was prepared by depositing alumina followed by iron using two different methods as described earlier. Characterization analysis revealed that aligned multiwalled carbon nanotubes array of 107.9 µm thickness grown by thermal chemical vapor deposition technique can only be achieved for the sample with iron deposited using ferrocene vaporization. The thick layer of partially oxidized iron film can prevent the deactivation of catalyst and thus is able to sustain the growth. It also increases the rate of permeation of the hydrocarbon gas into the catalyst particles and prevents agglomeration at the growth temperature. Combination of alumina-iron layer provides an efficient growth of high density multiwalled carbon nanotubes array with the steady growth rate of 3.6 µm per minute for the first 12 minutes and dropped by half after 40 minutes. Thicker and uniform iron catalyst film obtained from ferrocene vaporization is attributed to the multidirectional deposition of particles in the gaseous form.